Clays and Clay Minerals, Vol. 58, No. 5, 644–666, 2010. - Bozkaya, Omer; Yalcin, Huseyin (The Clay Minerals Society, 2010)
The Antalya Unit, one of the allochthonous units of the Tauride belt, is of critical, regional tectonic importance because of the presence of rifting remnants related to the break-up of the northern margin of Gondwana during Triassic time. Paleozoic-Mesozoic sedimentary rocks of the Antalya Unit consist mainly of calcite, dolomite, quartz, feldspar, and phyllosilicate (illite-smectite, smectite, kaolinite, chlorite, illite, chlorite-smectite, and chlorite-vermiculite) minerals. Illite-smectite (I-S) was found in all of the sequences from Cambrian to Cretaceous, but smectite was only identified in Late Triassic-Cretaceous sediments. R0 I-S occurs exclusively in early-diagenetic Triassic-Cretaceous units of the Alakırc¸ay Nappe (rift sediments), whereas R3 I-S is present in late-diagenetic to low-anchimetamorphic Cambrian-Early Triassic units of the Tahtalıdag˘ Nappe (pre-riftsediment s). Ku¨ bler Index (KI) values and the illite content of I-S reflect increasing diagenetic grades along with increasing depth. Majorelement, trace-element, rare-earth-element (REE), and stable-isotope (O and H) compositions were investigated in dioctahedral and trioctahedral smectites and I-S samples from the pre-rift and rift-related formations. Both total layer charge and interlayer K increase, whereas tetrahedral Si and interlayer Ca decrease from smectite to R3 I-S. Trace-element and REE concentrations of the I-S are greater in pre-rift sediments than in rift sediments, except for P, Eu, Ni, Cu, Zn, and Bi. On the basis of North American Shale Composite (NASC)-normalized values, the REE patterns of I-S in the pre-rift and rift sediments are clearly separate and distinct. Oxygen (d18O) and hydrogen (dD) values relative to SMOW (Standard Mean Oceanic Water) of smectite and I-S reflect supergene conditions, with decreasing d18O butincrea sing dD values with increasing diagenetic grade. Lower dD values for these I-S samples are characteristic of rift sediments, and pre-rift sediments have greater values. On the basis of isotopic data from these I-S samples, the diagenesis of the Antalya Unit possibly occurred under a high geothermal gradient (>35ºC/km), perhaps originating under typical extensional-basin conditions with high heat flow. The geochemical findings from I-S and smectites were controlled by diagenetic grade and can be used as an additional tool for understanding the basin maturity along with mineralogical data.
Geochemistry Of Mixed-layer Illite-smectites From An Extensional Basin, Antalya Unit, Southwestern Turkey
gsccm58505-boz.pdf -- 1,780KB
Keywords: Periodicals; Geology; I-S Mineralogy; Major Elements; O-H Isotopes; Trace Elements